Pertumbuhan Semai Jarak Pagar (Jatropha curcas L. ) Asal Biji Dan Stek Yang Ditanam Pada Jenis Tanah Berbeda - Prihastanti, Erma - (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2011)
The successful of the growth of Jatropha curcas L. in seed yield is affected when the nursery, such as howthe provision of seedlings and the media used. Jatropha propagation is generally done through vegetativepropagation (cuttings) and reproductive (seed).. Several efforts to maximize the quality of seedlings of which is withthe selection of appropriate planting medium, as in the choice of soil. This study aims to assess the growth ofjatropha seedlings from seeds and cuttings in different soil types. Research conducted at the Laboratory of Plant TestBogor Agricultural University, in February - July 2006. Jatropha seedlings used a month old from seed and cuttingsfrom parent trees were 8 years old. The growing medium used in the form of latosol and podzolic soil. Observationof growth after two months of maintenance performed by observing the plant wet weight, leaf number and length ofseedling roots.The results showed the growth of jatropha seedlings influenced by seedling origin and type of soil. Jatrophaseedlings from seeds or cuttings are planted in latosol or atosol increased wet weight, root length and number ofleaves for two months of the nursery. The best growth from seeds of jatropha seedlings when planted in soil latosol,while seedlings from cuttings better if planted in soil podzolic.